The impact of environmental management accounting adoption on the shipping industry's environmental performance, influenced by Green Shipping and Regulatory Pressure / Maulita, Amiril Azizah and Fabiola B Luturmas - Mursandi, Maulita; Azizah, Amiril; B Luturmas, Fabiola (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
The concept of sustainability within the realm of the industry is closely related to sustainable development. In East Kalimantan's shipping industry, environmental concerns related to the Mahakam River, carbon emissions, and international regulations have created a pressing need to adopt Green Shipping practices. The pressing need for Green Shipping practices stems from the accountability of the shipping industry in this context. The aim of this research was to explore the consequences of Green Shipping and Regulatory Pressure on the implementation of environmental management accounting (EMA) techniques in the maritime sector, specifically in East Kalimantan, as well as its subsequent effect on Environmental Performance. This is a quantitative study. The sample for this research was a shipping company registered with the Indonesian National Shipowners Association (INSA). The survey subjects were operational managers from a shipping company, and they were chosen because they possessed substantial knowledge about environmental accounting and shipping regulations. This study emphasizes that the adoption of Environmental Management Accounting (EMA) is influenced positively and significantly by Green Shipping and Regulatory Pressure, and it also has an impact on environmental performance. The study demonstrates that the shipping industry's adoption of EMA is influenced by Green Shipping and Regulatory Pressure. Environmental Management Accounting (EMA) is an essential instrument utilized by organizations in the shipping industry to evaluate the financial implications of their environmental activities and to divulge pertinent information regarding their environmental performance. This, in turn, facilitates the enhancement of their overall environmental performance.